Mixed Matrix Membranes Incorporated With Palladium Nanoparticles For Hydrogen Separation - Suhaimi, Hani Shazwani Mohd (2018)
An innovation in hydrogen (H2) selective membrane holds the important key to hydrogen economy. Polymers are the most practical and economical material for membrane fabrication, but the application of polymeric membranes including polysulfone (PSf) and polybenzimidazole (PBI) membranes in H2 separation is always limited by the “trade-off” between selectivity and permeability. In this work, Pd nanoparticles are incorporated into PSf and PBI membranes to overcome the mentioned limitations. Before blending, Pd nanoparticles were kinetically synthesized and stabilized in the inversed microemulsion of polyethylene glycol (PEG) or polyvinylpyrrolidone (PVP). The PSf mixed matrix membranes (MMMs) were prepared by dry-wet phase inversion while the dense PBI MMMs were synthesized by dry phase inversion. The X-ray diffraction (XRD) and Energy dispersive X-ray (EDX) results confirmed that the Pd nanoparticles incorporation was successful. The PSf(PEG/Pd)_3 MMM showed the highest separation performance (pure gas H2/N2 selectivity : 21.69, pure gas H2/CO2 selectivity: 1.98 and H2 permeability : 161.84 Barrer) among the PSf membranes blended with Pd nanoparticles in PEG. The addition of PEG induced the changes of finger-like structure into closed cells and the growth of dense layer. High H2 permeability was achieved using 2 wt% of Pd nanoparticles loading in PVP for PSf membrane (pure gas H2/N2 selectivity : 20, pure gas H2/CO2 selectivity : 6.2 and H2 permeability : 5781.07 Barrer). The improvement could be related to the changes of free volume in polymer and the growth of dense layer caused by PVP. At 200°C, PBI MMMs with remarkable thermal stability achieved excellent H2/CO2 and H2/N2 selectivities when 2 to 4 wt% of Pd nanoparticles in PEG were incorporated. The H2/CO2 selectivity of PBI(Pd/PEG)_2 membrane was 18.56 (H2 permeabillity : 53.22 Barrer) while the H2/N2 selectivity of PBI(Pd/PEG)_4 membrane was 108.28 (H2 permeabillity: 62.40 Barrer). A higher selectivity of H2 was achieved by using PVP as the stabilizer in PBI(Pd) MMMs in comparison to the PBI(Pd) MMMs with PEG. The PBI(Pd/PVP)_1 membrane with 1 wt% of Pd nanoparticles loading in PVP achieved a pure gas H2/CO2 selectivity of 19.73 and a pure gas H2/N2 selectivity of 252.54 (H2 permeabillity : 32.41 Barrer). Both PBI(Pd/PEG)_2 and PBI(Pd/PVP)_1 membranes surpass the upper bound of Robeson plot successfully. For PBI membranes, the diffusion coefficients depend on temperature strongly with minimal contribution of solubility into gas selectivity and permeability. The activation energy reduced greatly in PBI MMMs and it could signify the reduction of gas diffusion due to a drop in free volume. However, the preferential sorption of H2 in all MMMs with Pd nanoparticles could be related to the H-Pd interaction. Eventhough the permeation behavior is different between pure and mixed gas permeation due to their transport behavior, the PBI(Pd/PVP)_1 MMMs for mixed gas showed an impressive improvement of H2 in permeate compare to neat PBI membrane for 50/50 ratio. The 98.7 % H2 purity was achieved at 90 % H2 recovery. In this study, Pd nanoparticles loading and operating temperature gave significance effect on purity and recovery of H2 due to the changes on permeability and selectivity of membrane.